A novel graphite-like stacking structure in a discrete molecule and its molecular recognition behavior. (10th May 2018) - Akine, Shigehisa; Onuma, Takahiro; Nabeshima, Tatsuya
Abstract : Macrocyclic imines containing two hexabenzocoronene planes adopted a unique intramolecular stacking structure, similar to the stacking pattern in natural graphite. Abstract : A graphite-like stacking structure was nicely reproduced in a discrete molecule that was prepared by 2+2 macrocyclic Schiff base formation. In the crystal structure, two hexabenzocoronene planes are closely stacked with displacement, yielding the intramolecular stacking structure similar to an AB- or ABC-stacking pattern in natural graphite. This molecule showed a recognition ability toward electron-deficient aromatic molecules in solution.